The relationship between the emotional intelligence of entrepreneurs and the new venture creation: The role of age, gender and motive - Hadia Fakhr El-Din (Arab Economic and Business Journal, 2017)
The study investigates the effect of emotional intelligence (EI) of entrepreneurs on new venture creation (NVC). A self-administered questionnaire is used to test the study hypothesis on a sample of 378 Egyptian entrepreneurs. The analysis shows that there is a significant relationship between emotional intelligence and new venture creation. There are three constructs of EI (interpersonal skills, internal motivation and self-awareness), which support the creation of new ventures. The results of the empirical study are validated using demographic characteristics (age and gender) and the motivation of entrepreneurship (necessity-driven or opportunity-driven). The findings show that age has a moderating effect on the relationship between EI and NVC, whereas gender does not play a role in this relationship. There are differences in the relationship between emotional intelligence and new venture creation based on the motivation to engage in entrepreneurship. Although the relationship is significant in the cases of both necessity-driven and opportunity-driven entrepreneurs, the dimensions/ constructs of EI that support the new venture creation are different in each case.
Keywords: 650; Emotional intelligence; Entrepreneurship; Motive; New venture creation; Egypt